Protective Effect of Artemisia argyi and Its Flavonoid Constituents against Contrast-Induced Cytotoxicity by Iodixanol in LLC-PK1 Cells - Lee, Dahae; Kim, Chang-Eop; Park, Sa-Yoon; Kim, Kem Ok; Hiep, Nguyen Tuan; Lee, Dongho; Jang, Hyuk-Jai; Lee, Jae Wook; Kang, Ki Sung (MDPI, 2018)
Preventive effects and corresponding molecular mechanisms of mugwort (Artemisia argyi) extract and its flavonoid constituents on contrast-induced nephrotoxicity were explored in the present study. We treated cultured LLC-PK1 cells with iodixanol to induce contrast-induced nephrotoxicity, and found that A. argyi extracts ameliorated the reduction in cellular viability following iodixanol treatment. The anti-apoptotic effect of A. argyi extracts on contrast-induced nephrotoxicity was mediated by the inhibition of mitogen-activated protein kinase (MAPK) phosphorylation and the activation of caspases. The flavonoid compounds isolated from A. argyi improved the viability of iodixanol-treated cells against contrast-induced nephrotoxicity. Seven compounds (1, 2, 3, 15, 16, 18, and 19) from 19 flavonoids exerted a significant protective effect. Based on the in silico oral-bioavailability and drug-likeness assessment, which evaluate the drug potential of these compounds, compound 2 (artemetin) showed the highest oral bioavailability (49.55%) and drug-likeness (0.48) values. We further investigated the compound-target-disease network of compound 2, and proliferator-activated receptor gamma (PPAR-gamma) emerged as a predicted key marker for the treatment of contrast-induced nephrotoxicity. Consequently, compound 2 was the preferred candidate, and its protective effect was mediated by inhibiting the contrast-induced inflammatory response through activation of PPAR-gamma and inhibition of MAPK phosphorylation and activation of caspases.
Keywords: ACUTE KIDNEY INJURY; NF-KAPPA-B; ISCHEMIA-REPERFUSION INJURY; INDUCED APOPTOSIS; OXIDATIVE STRESS; ETHANOL EXTRACT; PPAR-GAMMA; IN-VITRO; INDUCED NEPHROPATHY; ASIATICA EXTRACT